Experiências agroecológicas em assentamentos do MST: A transição agroecológica em assentamentos do MST na PB - Luz, Marcel Silva (2022)
The issues of land concentration and land struggle are relevant guidelines of environmentalism in Brazil, social movements that take part in this discussion are the major actors from civil society. The Landless Rural Workers Movement (MST), the largest peasant movement in Latin America, in addition to a sociopolitical agenda, brings agroecology into its programmatic horizon as a paradigm of relationship between individual, society and nature. This research was developed in three settlements in agroecological transition, located in the Zona da Mata Paraibana and had as main objective to verify the potentialities and limits of the agroecological production systems developed by the MST-PB settlements. And as specific objectives: 1) to analyze the insertion of the environmental discussion in the MST agenda and the historical process of this acquisition; 2) to understand the symbolic meaning of agroecology for and in the MST; 3) to identify the settlers' resistance and also their agreements regarding the agroecological transition process; and 4) to inventory the particularities of agroecology in the MST experience. The literature review, field research, systematic observation, and application of semi-structured interviews were the tools used for gathering data. The manifest speeches were analyzed according to the categorical thematic content analysis method. The results of the evaluation of these discourses revealed that the agroecology practiced by and existing in the MST program has its own characteristics not because of the Movement in itself, but related to its application by a peasant movement that participates in the struggle for land and in the movement for environmental justice. Agroecology is seen by the MST not only as a new paradigm of knowledge, but as a strategic horizon and a praxis involved in the class struggle. It was also evident that the agroecological transition for the MST-PB has its own contours, acquiring a permanent character in the face of productive limitations in the settlements and in the name of preserving something essential to the Movement, which is the production of food for the population.